Pengaruh Metode Bermain Terhadap Kemampuan Passing Sepakbola SMAN 1 Telukjambe Barat - Bayu Segara Wicaksana; Abduloh Abduloh; Setio Nugroho (Peneliti.net, 2022)
Learning methods are very important in supporting success in achieving learning objectives, so this study aims to improve the football passing ability of the students of SMAN 1 Telukjambe Barat, because there are still students who have not mastered football passing techniques or have not been maximized. This study adopted a set of experimental methods. designed before and after testing. The data collection carried out in this study used a football passing test. The subjects of this study were high school students as many as 100 students. This can be seen from the implementation of the research that the final test is better than the initial test in changing the pretest and posttest. It can be concluded that the playing method is useful for learning football passing skills and techniques. This level affects the basic passing ability of students' football as a whole including in the good category, so that the playing method can be applied in learning football.